2016
DOI: 10.1080/15389588.2016.1205190
|View full text |Cite
|
Sign up to set email alerts
|

Neck forces and moments of human volunteers and post mortem human surrogates in low-speed frontal sled tests

Abstract: This study examined the effects of active muscles, in the form of conscious and reflexive muscle activity, on the biomechanical response of occupants in low-speed frontal sled tests. Although active bracing did not result in significantly different peak neck loads or moments, the timing of these peak values were affected by muscle condition. The findings of this study provide insight to the kinetics experienced during low-speed sled tests and are important to consider when refining and validating computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…The mean head excursion was significantly influenced by the awareness and was decreased for the aware trials to 140.8 ± 38 mm ( Table 1 ), compared to 168 ± 35 mm at the peak deceleration of the sled (2.6 g) in the previous study [ 36 ]. Beeman et al [ 11 , 12 , 13 ] observed a 124 ± 9 mm head excursion at 2.5 g for relaxed volunteers in the driver’s position with the arms acting against the steering wheel. Ólafsdóttir et al [ 20 ] found a similarly reduced head excursion contributed to the reflexive response evoked by the belt pre-tensioner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean head excursion was significantly influenced by the awareness and was decreased for the aware trials to 140.8 ± 38 mm ( Table 1 ), compared to 168 ± 35 mm at the peak deceleration of the sled (2.6 g) in the previous study [ 36 ]. Beeman et al [ 11 , 12 , 13 ] observed a 124 ± 9 mm head excursion at 2.5 g for relaxed volunteers in the driver’s position with the arms acting against the steering wheel. Ólafsdóttir et al [ 20 ] found a similarly reduced head excursion contributed to the reflexive response evoked by the belt pre-tensioner.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic data from the motion capture were used for the planar-inverse-dynamics analysis to estimate the neck-muscle loads during the impact [ 13 , 36 , 41 , 42 ]. The head was considered as a rigid body connected to the neck at the occipital condyles (OC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle activity can affect the body posture and dynamic response of the occupant’s body in low-velocity vehicle collisions, evasive braking, and steering manoeuvres (as well as deployment of autonomous collision avoidance systems) [1,2,3,4,5,6]. Bracing and occupant body dynamics may also influence the injury outcome in low-severity impacts [7].…”
Section: Introductionmentioning
confidence: 99%
“…Anderst et al [34] used the inverse dynamics approach to estimate neck muscle forces, where in vivo motion data was used to drive a numerical model of the head-neck complex, but for slow voluntary motion only. Funk et al [35] verified that the inverse dynamics approach can be used for the neck load estimation in case of impact forces acting to the head, while Seacrist et al [36] and Beeman et al [2,3,4] analysed volunteers’ neck loads during low-velocity frontal impacts. However, the joint moment results from the action of the whole muscle group, the electrical activity of which cannot be assessed with a single EMG electrode, making it difficult to correlate the EMG signal to the body dynamic response directly.…”
Section: Introductionmentioning
confidence: 99%